HE4 has a High Diagnostic Value to Detect Epithelial Ovarian Cancer: HE4 Memiliki Nilai Diagnostik yang Tinggi untuk Mendeteksi Keganasan Ovarium Tipe Epitel - Bismarck J. Laihad; Hariyono Winarto; Bambang Sutrisna (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To find out the diagnostic value of CA125 and HE4 as a tumor marker, and also RMI and ROMA as a malignancy predictor in patients with ovarian tumors. Methods: This study was a diagnostic study using cross-sectional design.This study was performed in Jakarta from November 2010 to May 2011. One hundred and twenty eight serum samples of patients diagnosed with ovarian tumors were collected before undergoing surgery in Dr. Cipto Mangunkusumo General Hospital. The CA125 and HE4 levels were then examined. The histopathological examination of tissue specimens were performed in Department of Pathology Anatomy in RSCM. For statistical analysis, we used a 2x2 table to produce ROC-AUC curve. Results: The median value of HE4 and CA125 serum concentrations was higher and more significant on patients with ovarian malignancy than patients with benign ovarian tumor (p<0.05). Using the cut-off standard, HE4 had the highest accuracy value (76.5%). On the premenopausal group, HE4 and ROMA had the same AUC value, that is 85.0 % (95% CI: 0.73-0.96), whereas on the postmenopausal group, ROMA had the highest AUC value of 96.9 % (95% CI: 0.92-1.00). Conclusion: HE4 has a high diagnostic value as a single tumor marker to detect epithelial ovarian cancer and its combination with CA125 (ROMA) gives an even better result. Keywords: epithelial ovarian cancer, human epididymis protein 4, risk of ovarian malignancy algorithm, tumor marker